Appearance, texture and flavour improvement of chocolate bar by Virgin Cococnut Oil (VCO) as Cocoa Butter Substitute (CBS) - Eti Indarti; Normalina Arpi; Heru P. Widayat; Ashabul Anhar (Syiah Kuala University, 2013)
The purposes of using CBS in this research is to improve the physical properties and quality of appereance and structure stability of chocolate bar. Based on chemical composition, CBS and Cocoa butter have different profile, but they have similar physical properties due to high lauric acid content. The advantage of lauric acid is to affect shinny appreance of chocolate surface, and also soapy taste that closely related to rancidity reduction. Virgin Coconut Oil (VCO) is one of lauric fat that easily found in Aceh. In this research, chocolate bar is formulated comprising various concentration of CBS (0,1,2,3,4,5%) with respect to cocoa butter, and cocoa mass composition (200 g and 300 g). It was found that melting point was affected by CBS concentration. The higher CBS concentration, the lower melting point of chocolate bar. An increase in VCO concentration reduced significantly the melting point of chocolate bar. Melting point was comparable to other chocolate bar commercial (29-32oC). The unblooming, snap, best texture and better taste was observed for the chocolate bar containing 4-5% of VCO concentration and 27,5% of cocoa mass